Occupations and health - Brendan Walsh; Karina Doorley (The Economic and Social Research Institute (ESRI), 2022)
The relationship between health and employment status continually shows that individuals who work have lower levels of illness and higher self-reported health. This study examines how self-reported health and objective measures of health (multimorbidity and mental health problems) differ across employment status and occupations among adults of working age (25-65 years). In addition, the study examines how public health coverage - medical card and GP visit card (GPVC) - and private health coverage (PHI), and lack thereof, differ across occupations. Overall, individuals not in employment have much lower rates of self-reported health and higher rates of illness. In particular, mental health problems are three times higher among unemployed individuals across all age groups. Examining workers separately, differences in health status across occupations are small. However, rates of health coverage differ considerably across occupations. In general, occupations associated with poorer health status tend to have the highest percentages of workers without a medical card/GPVC or PHI. This affects workers' ability to access lower cost or free healthcare, including for the purpose of certified sick leave.
Keywords: 330; Gesundheit; Psychische Störung; Gesundheitsversorgung; Beruflicher Status; Bildungsniveau; Irland